An optimised failure envelope approach of bucket foundation in undrained clay. (17th December 2021) - Wang, Jiayu; Liu, Run; Yang, Xu; Chen, Guangsi
ABSTRACT: The bucket foundation is a new type foundation which is suitable for offshore wind turbines. The failure envelope is used to check the bearing capacity under combined loading conditions, especially for foundations with irregular shapes. Due to the coupling effect between horizontal and moment loads, the H-M failure envelope has an obvious asymmetry, which makes the established algebraic equation of the envelope form complex and inconvenient to apply. In this paper, an optimised failure envelope is proposed to reduce the coupling degree between horizontal and moment loads by moving the load reference point to the rotation centre of bucket foundation. Furthermore, the algebraic equation of the failure envelope is established based on the optimised envelope by using the depth of the bucket foundation rotation centre. The equation has fewer parameters and clearer physical meanings than the conventional one, which is convenient for engineering applications.